Response to Prof. Meghan J. Clark’s “Equal Dignity and Agency: Catholic Social Teaching & The Lives of Women” - McGrath, Aoife (Irish theological quarterly, 2025)
This article has its origins in an invited response paper to Prof. Meghan J. Clark’s Irish Theological Quarterly lecture at St Patrick’s Pontifical University, Maynooth, on 14 October 2024. While incorporating many elements of the original response, it has been revised and expanded to also serve as a response to the article version of Prof. Clark’s lecture which is published in the current issue.